(untitled) (City: History, Culture, Society, 2023)
Now more than ever, an unbiased, careful, and critical approach to Russian literature is necessary, in particular to that category of literature that critics read as apolitical, since available studies, unfortunately, often do not reflect the real state of affairs, hide facts that do not fit into the traditional imperial cultural mythology, and generally performed within the established ideology. This paper examines the construction of the imperial identity of Joseph Brodsky, a Russian poet, essayist, public intellectual, and Nobel Laureate since 1986. Using the example of the Watermark essay, we analyse one of the signs of imperialism in Brodsky’s work, namely the colonial attitude towards women, the motif of the conquest of the city, and the conquest of the woman. The study focuses on the author’s myth of Brodsky and how it correlates with the motif of the conquest of Venice in the «Watermark» essay.